2014
DOI: 10.1113/jphysiol.2014.276527
|View full text |Cite
|
Sign up to set email alerts
|

Differential phospholipase C‐dependent modulation of TASK and TREK two‐pore domain K+ channels in rat thalamocortical relay neurons

Abstract: Key pointsr During the behavioural states of sleep and wakefulness thalamocortical relay neurons fire action potentials in high frequency bursts or tonic sequences, respectively.r The modulation of specific K + channel types, termed TASK and TREK, allows these neurons to switch between the two modes of activity.r In this study we show that the signalling lipids phosphatidylinositol 4,5-bisphosphate (PIP 2 ) and diacylglycerol (DAG), which are components of their membrane environment, switch on and shut off TRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 69 publications
(188 reference statements)
2
42
0
1
Order By: Relevance
“…Based on the prevention of ATPinduced I TREK-2,i-o suppression by PI-kinase inhibitors (wortmannin or LY29402) and the inhibition by PI(4,5)P 2 [16,27,36], we proposed that TREK-2 inhibition by intracellular ATP is mediated by membrane-delimited production of PI(4,5)P 2 . However, our model of tonic intrinsic inhibition of TREK-2 by PI(4,5)P 2 has not yet been confirmed by other researchers.…”
Section: Introductionmentioning
confidence: 45%
See 2 more Smart Citations
“…Based on the prevention of ATPinduced I TREK-2,i-o suppression by PI-kinase inhibitors (wortmannin or LY29402) and the inhibition by PI(4,5)P 2 [16,27,36], we proposed that TREK-2 inhibition by intracellular ATP is mediated by membrane-delimited production of PI(4,5)P 2 . However, our model of tonic intrinsic inhibition of TREK-2 by PI(4,5)P 2 has not yet been confirmed by other researchers.…”
Section: Introductionmentioning
confidence: 45%
“…In subsequent reviews, Chemin et al demonstrated that PI(4,5)P 2 inhibited TREK-1 in about half of i-o patches on COS-7 cells and hippocampal neurons [3,5]. Nevertheless, most relevant studies and reviews by other researchers regard PI(4, 5)P 2 as a stimulatory factor of TREKs [2,11,30,31,33].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, DAG could be identified as TASK-channel inhibitor in further experiments with heterologously expressed channels in which genetic sensors for PIP 2 and DAG have been used. These results could be recently confirmed in native neurons [21]. In this context, the signalling lipids, DAG and PIP 2 are obviously components of the membrane environment in which TASK-and TREK-channels are embedded.…”
Section: Muscarinic Inhibition Of K 2p -Channelsmentioning
confidence: 53%
“…It could be demonstrated through the combination of electrophysiological and molecular biological techniques that TASK-1-, TASK-3-, and TREK-1-channels underlie this adjustable potassium-leak conductance in relay neurons [17][18][19][20][21]. Moreover, inhalation anaesthetics like halothane and isoflurane induce a hyperpolarization of relay neurons by activating K 2P -channels which is accompanied by increased burst activity [22].…”
Section: The Thalamocortical Systemmentioning
confidence: 98%